2018
DOI: 10.1158/1078-0432.ccr-18-0991
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Functional Evaluation of Variants of Unknown Significance in ERBB2

Abstract: The advent of next-generation sequencing technologies has enabled the identification of several activating mutations of Erb-B2 receptor tyrosine kinase 2 (ERBB2) among various cancers. However, the significance of infrequent mutations has not been fully investigated. Herein, we comprehensively assessed the functional significance of the mutations in a high-throughput manner. We evaluated the transforming activities and drug sensitivities of 55 nonsynonymous mutations using the mixed-all-nominated-in-one (MANO)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(88 citation statements)
references
References 49 publications
7
81
0
Order By: Relevance
“…But generally, compared with other variants, HER2 YVMA insertion correlated with significantly worse clinical outcomes on afatinib (ORR, 0%; median PFS, 1.2 months; 95% CI, 0–2.4). In accordance with our results, Nagano et al reported higher half maximal inhibitory concentration of afatinib against A775_G776insYVMA compared with G776delinsVC and V777L in preclinical models .…”
Section: Discussionsupporting
confidence: 93%
“…But generally, compared with other variants, HER2 YVMA insertion correlated with significantly worse clinical outcomes on afatinib (ORR, 0%; median PFS, 1.2 months; 95% CI, 0–2.4). In accordance with our results, Nagano et al reported higher half maximal inhibitory concentration of afatinib against A775_G776insYVMA compared with G776delinsVC and V777L in preclinical models .…”
Section: Discussionsupporting
confidence: 93%
“…It is important to note that wild-type BRCA2 -induced cells were significantly more sensitive than parental DLD1 cells; therefore, we should establish a sensitive method in which all comparisons could be made with wild-type-induced cells rather than parental cells. We thus modified the mixed-all-nominated-in-one (MANO) method 28,29 that was originally developed to enable high-throughput evaluation of VUSs in transforming genes and invented the MANO- BRCA (MANO-B) method for the functional evaluation of BRCA2 variants ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The original MANO method is a high-throughput functional assay previously reported by our laboratory 28,29 . Individually established DLD1 BRCA2 (-/-) cells with stable BRCA2 expression were mixed equally and cultured competitively.…”
Section: Methodsmentioning
confidence: 99%
“…This mutation lies within the protein kinase domain of the HER2 protein, although the functional status of the protein alteration remains controversial. Two studies identified I767M as a gain‐of‐function mutation with transformative potential, resulting in increased HER2 kinase activity and sustained AKT phosphorylation . However, another study demonstrated no difference in cell proliferation or viability of HER2 I767M compared to wild‐type HER2 .…”
Section: Discussionmentioning
confidence: 99%
“…Two studies identified I767M as a gain-of-function mutation with transformative potential, resulting in increased HER2 kinase activity and sustained AKT phosphorylation. 19,20 However, another study demonstrated no difference in cell proliferation or viability of HER2 I767M compared to wild-type HER2. 21 HER2 mutations have been well studied in breast cancer, including HER2 nonamplified breast cancer.…”
Section: Case Reportmentioning
confidence: 98%